MicroRNA-26a/b have protective roles in oral lichen planus - Du, Jie (Cell Death Dis, 2020)
Oral lichen planus (OLP) is a kind of oral epithelial disorder featured with keratinocyte apoptosis and inflammatory reaction. The pathogenesis of OLP remains an enigma. Herein, we showed that the levels of miR-26a/b were robustly down-regulated in oral mucosal biopsies, serum and saliva in OLP patients compared with healthy control. Moreover, we found the binding sites of vitamin D receptor (VDR) in the promoter regions of miR-26a/b genes and proved that the induction of miR-26a/b was VDR dependent. The reduction of miR-26a/b expression was also detected in the oral epithelium of vitamin D deficient or VDR knockout mice. miR-26a/b inhibitors enhanced apoptosis and Type 1T helper (Th1) cells-related cytokines production in oral keratinocytes, whereas miR-26a/b mimics were protective. Mechanistically, we analyzed miRNA target genes and confirmed that miR-26a/b blocked apoptosis by directly targeting Protein Kinase C δ (PKCδ) which promotes cellular apoptotic processes. Meanwhile, miR-26a/b suppressed Th1-related cytokines secretion through targeting cluster of the differentiation 38 (CD38). In accordant with miR-26a/b decreases, PKCδ and CD38 levels were highly elevated in OLP patients’ samples. Taken together, our present investigations suggest that vitamin D/VDR-induced miR-26a/b take protective functions in OLP via both inhibiting apoptosis and impeding inflammatory response in oral keratinocytes.